2003
DOI: 10.1029/2003jd003712
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of NO2 by the photolysis conversion technique during the Transport and Chemical Evolution Over the Pacific (TRACE‐P) campaign

Abstract: [1] An airborne instrument for in situ measurements of tropospheric nitrogen dioxide (NO 2 ) was developed using the photolytic conversion technique followed by chemiluminescence detection of NO. This instrument was used for the measurements of NO 2 on board the NASA P-3B aircraft during the Transport and Chemical Evolution Over the Pacific (TRACE-P) campaign. Comparison in the laboratory indicated less than 10% difference between our NO 2 instrument and two independent laser-induced fluorescence instruments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Similar values from different campaigns can be found in Warneck (2000). Ratios of up to 1 are found in the middle troposphere (Nakamura et al, 2003).…”
Section: No 2 Chemistrysupporting
confidence: 72%
See 2 more Smart Citations
“…Similar values from different campaigns can be found in Warneck (2000). Ratios of up to 1 are found in the middle troposphere (Nakamura et al, 2003).…”
Section: No 2 Chemistrysupporting
confidence: 72%
“…Furthermore, the NO 2 concentration is affected by the partitioning of NO x into NO and NO 2 which depends on the meteorological conditions, the abundance of reactive organic compounds and the altitude in the troposphere. During the Transport and Chemical Evolution over the Pacific (TRACE-P) campaign between February and April 2001 (Jacob et al, 2003), the bulk of the NO/NO 2 ratios have been found to be around 0.25 at near-ground levels (Nakamura et al, 2003). Similar values from different campaigns can be found in Warneck (2000).…”
Section: No 2 Chemistrysupporting
confidence: 70%
See 1 more Smart Citation
“…A good agreement was also observed with results from the DOAS system for a 2‐day period. Nakamura et al [2003] compared a photolytic converter instrument with two LIF instruments. Their laboratory tests revealed agreements with the LIF instruments of less than 10% difference.…”
Section: Introductionmentioning
confidence: 99%
“…The most common measurement technologies for NO x are based on the chemiluminescence detection (CLD) for the indirect measurement of NO (Clough and Thrush, 1967;Ridley and Howlett, 1974;Drummond et al, 1985;Fahey et al, 1985). CLD instruments have often been coupled to a photolytic or catalytic converter to measure NO 2 and NO x by using a xenon lamp, blue-light converter or catalytic conversion of NO 2 into NO, prior to the CLD unit Ryerson et al, 2000;Nakamura et al, 2003;Pollack et al, 2010;Villena et al, 2012;Reed et al, 2016). NO 2 measurements at low-NO x conditions (below 0.1 ppbv) are close to the limit of detection (Yang et al, 2004), and depending on the installed converter each instrument might show interferences with other nitrogen-oxide-containing species (e.g., Reed et al, 2016).…”
Section: Introductionmentioning
confidence: 99%